2013
DOI: 10.4028/www.scientific.net/amr.838-841.454
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Selected Materials to Create Sliding Joint in the Foundation Structure

Abstract: Some foundation structures can be loaded with horizontal stress, for example pre-stressed foundation structures or structures on undermining areas. Then it is necessary to solute their effects, because they can have very significant effect on the building. When it is spoken about the foundation structures which are loaded with horizontal stress then it is spoken about two possibilities of this loading. In the first case there are horizontal deformations in the structure and in the second case these deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…It is very convenient to design the prestressed foundation structures for undermined territories, as the prestress and the slip strip can be combined, eliminating thus efficiently adverse tensile stress in the reinforced concrete section, see [22], [23], [24], [25]. Measurements within the existing prestressed structures of the foundation under the rack hall in Ostrava [6] have showed that the slip strip was efficient, as 80% of longitudinal displacements occurred within the slip strip.…”
Section: Pre-stressed Foundation Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very convenient to design the prestressed foundation structures for undermined territories, as the prestress and the slip strip can be combined, eliminating thus efficiently adverse tensile stress in the reinforced concrete section, see [22], [23], [24], [25]. Measurements within the existing prestressed structures of the foundation under the rack hall in Ostrava [6] have showed that the slip strip was efficient, as 80% of longitudinal displacements occurred within the slip strip.…”
Section: Pre-stressed Foundation Structuresmentioning
confidence: 99%
“…Displacement and friction between the plate and subsoil causes tensile stress, decreasing the pressure stress, caused by the prestress, towards the middle of the foundation. To solve the task, it is possible to use a similar phenomenon that occurs in structures erected on undermined territories, see [22], [23], [24], [25] and [26] for instance.…”
Section: Fig 1 Prestressed Force and Course Of Contact Stress Below P...mentioning
confidence: 99%
“…from the point of view of concrete mixture, reinforcement, slab dimensions and its thickness or size of the load area. Process, results and conclusions of the performed loading tests are described in [6,7,8].…”
Section: Experimental Loading Testsmentioning
confidence: 99%
“…Currently the experimental measurements of stress and strain of foundation structures in connection with the subsoil-structure interaction are also conducted at the Department of Structures, Faculty of Civil Engineering, VSB -TU Ostrava. Other fields of research are focused on the use of sliding joints to eliminate friction between the foundation and subsoil [10,11] and prestressing of foundation structures [12] (the numerical solution). At the Faculty of Civil Engineering, an unique test equipment was constructed in order to measure the shear resistance of the sample from asphalt belts.…”
mentioning
confidence: 99%
“…During testing of the asphalt belts the shear resistance of the sample depending on the temperature is measured in a climatic chamber. The process, results and conclusions of tests are described in detail in [10,13]. In 2010, the construction of test equipment called Stand was performed at the Faculty of Civil Engineering [14].…”
mentioning
confidence: 99%